Effect of Crude Aqueous Extracts of Some Medicinal Plant Flowers on Solid Ehrlich Tumor in Mice - Erian, N; Hamed, H; El-Khateeb, A; Farid, M (Arab Journal for Sciences and Research Publishing, 2016)
Crude aqueous extracts of Cynara Cardunculus, Achillea millefolium, Calendula officinalis and Matricaria chamomilla flowers belong to family Compositeae were used in this work to study their efficiency to relief solid ehrlich tumor in mice. The more effective extract was C. officinalis which decreased tumor size from 513.6 to 139.8mm at a dose of 200mg/kg body weight comparing with doxorubicin which reduced tumor size to 98.2mm in concentration of 15mg/kg after 21 days, followed by M. chamomilla which showed the mean value of 168.7mm. While, the lowest values were showed with C. cardunculus and A. millefolium flowers extract which were 198.7 and 223.5mm, respectively. Also, the more effective treatments were doxorubicin in concentration of 15mg/kg and C. officinalis, followed by M. chamomilla, C. cardunculus and A. millefolium flowers extract for blood tests in tumor mice, e.g. antioxidant markers (MDA, TAC, SOD), liver functions (ALT, AST, Total proteins, Albumin and Globulins), kidney functions (Creatinine and Urea) lipid profile (triglycerides, total cholesterol, HDL, LDL and vLDL) and haematological parameters (HB, RBCs, Plt and WBCs) comparing with control tumor mice at a dose of 200mg/kg body weight for 21 days.